2008
DOI: 10.1109/tsp.2008.917375
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Cyclic Convolution Based on Recursive Formulations of Block Pseudocirculant Matrices

Abstract: In this paper, we show how novel recursive formulations of block pseudocirculant matrices lead to a new class of parallel cyclic convolution algorithms that exhibit a high degree of regularity and modularity and are suitable for parallel or pipelined implementation into today's very large scale integration (VLSI) circuits, multifield-programmable gate arrays (multi-FPGAs) systems, and multiprocessor architectures. In addition to the architectural advantages, the proposed formulations offer a comparable number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The recursive use of stride permutations was further developed in [4] in order to obtain reduced complexity parallel cyclic convolution.…”
Section: Previous Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The recursive use of stride permutations was further developed in [4] in order to obtain reduced complexity parallel cyclic convolution.…”
Section: Previous Workmentioning
confidence: 99%
“…We have shown that stride permutations acting on Circulant Matrices of composite size give Block Pseudocirculant Matrices, [2], [3], [4], [6], whose sub-blocks are themselves circulant and amenable to be processed in parallel. In mathematical notation, with N=r 0 s, it is as follows,…”
Section: B Blocking Circulant Matricesmentioning
confidence: 99%
See 3 more Smart Citations